Analisis Perkembangan Neraca Pembayaran Indonesia dan Implikasinya terhadap Manajemen Makroekonomi - Hutasoit, Elfhian Goklas Pangihutan; Jhon Kristopel Manalu; Remus Silalahi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Indonesia's Balance of Payments is a crucial indicator in assessing the country's economic performance. The Balance of Payments reflects all economic transactions between Indonesian residents and the international community over a specific period. The purpose of writing this paper is to analyze the development of Indonesia's Balance of Payments, the factors influencing it, and its implications for macroeconomic management policies. The method used is a literature study with a descriptive-analytical approach to Indonesia's economic data and policies. The results of the study indicate that the dynamics of Indonesia's Balance of Payments are significantly influenced by export-import performance, foreign capital flows, and the stability of the financial sector. Therefore, an integrated economic management strategy is needed to maintain external balance and support sustainable economic growth.